Analysis of trends and projections of the emergence, impact and the epidemiology of HIV/AIDS in Nigeria (2010)
The first case of AIDS was reported in Nigeria-(Lagos) in 1986. Since then, both the incidence and the prevalence of the epidemic has grown steadily, particularly during the military regimes. In this study, We used the UNAIDS softwares: Estimation and Projection Package-(EPP) and AIDS Impact Mode/-(AIM), to present models, trends analysis and projections/or the incidence a/HIVIAIDS in the six geopolitical zones in Nigeria. 0111' results show that the peak incidence 0/HIVIAIDS epidemics in the zones was during the Military rule in Nigeria. We also projected that by year 2010, the incidence are expected to be stable.